Liver retinol estimated by (13)C-retinol isotope dilution at 7 versus 14 days in Burkinabe schoolchildren - Bationo, Jean F (Exp Biol Med (Maywood), 2019)
Vitamin A status assessment is not straightforward. Retinol isotope dilution (RID) testing requires time for the tracer dose to mix with the total body stores of vitamin A (TBS). Researchers are interested in shortening the time interval between tracer administration and follow-up blood draws, and in re-examining current assumptions about liver mass for calculation of total liver vitamin A reserves (TLR, in µmol/g liver). Schoolchildren (aged 7–12 years; n = 72) were recruited from one school in Burkina Faso. After a baseline blood draw, 1.0 µmol [14,15]-(13)C(2)-retinyl acetate was administered to estimate TBS and TLR by retinol isotope dilution with follow-up blood samples at days 7 and 14. Correlations were determined to evaluate if sampling at day 7 could be used to predict TLR compared with day 14. Liver mass was estimated using body surface area and compared with the currently used assumption of liver weight equivalent to 3% of body weight. (This trial was registered at Pan African Clinical Trial Registry: PACTR201702001947398). Liver mass calculated using body surface area did not differ from the standard assumption of 3% of body weight and yielded similar TLR values. The children in this study had mean TLR (0.67 ± 0.35 µmol/g) in the adequate range, while serum retinol concentrations (0.92 ± 0.33 µmol/L) predicted 25% vitamin A deficiency. TLR values at seven days were highly correlated with, but significantly different from day 14 (P < 0.0001, r = 0.85) and needed a correction factor added to the equation to yield equivalency. Blood drawing at day 7, using correction factors in the prediction equation and the current assumption of liver mass as 3% of body weight, can be used to estimate TLR in schoolchildren with adequate vitamin A status in (13)C(2)-RID applications, but further investigations are needed to verify the seven-day predictive equation. IMPACT STATEMENT: Biomarkers of vitamin A status that reflect the gold standard, i.e. liver biopsy, are available but undergoing refinement to increase accessibility in community-based applications. Retinol isotope dilution testing is one such biomarker. Researchers are interested in decreasing the length of time between isotope administration and follow-up blood draws. This study compared a 7-day blood draw with a 14-day sample. With the simple addition of a correction factor to the prediction equation, the values for total body vitamin A stores were similar, but variation increased with increasing liver reserves. The assumption of 3% of body weight as liver weight in school-aged children was also investigated and confirmed as appropriate in the calculation for total liver vitamin A reserves. Simplifying isotope dilution for population evaluation and building capacity for mass spectrometry analyses are important areas of nutrition development to inform public health programs.